2014
DOI: 10.1186/1471-2393-14-360
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing the quality of preconception healthcare in China: applying a preconceptional instrument to assess healthcare needs

Abstract: BackgroundPreconception care is defined as the promotion of the health and well-being of a woman and her partner before pregnancy. Improving preconception health can result in improved reproductive health outcomes. China has issued latest version official guideline for preconception care in 2011. The objective of this cross-sectional study is to determine whether there is a variation in the quality of preconception healthcare services in distinct eastern and northern populations of China, and what factors are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
9
0
5

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 21 publications
6
9
0
5
Order By: Relevance
“…En 2006, los Centros para el Control y la Prevención de Enfermedades de Atlanta, en Estados Unidos (CDC, por sus siglas en inglés) publicaron recomendaciones para mejorar la salud preconcepcional y el cuidado médico 8 . Después, Países Bajos y Canadá han emitido sus propias recomendaciones nacionales para la atención preconcepcional 9 . La OMS, en 2012, presentó el "Plan de acción para acelerar la reducción de la mortalidad materna y mortalidad materna grave", proponiéndose como una medida concreta la organización de los servicios de salud para la atención de la mujer antes del embarazo, continuando con atención del embarazo, parto y puerperio, con el fin de reducir dicha mortalidad 10,11 .…”
Section: Resultsunclassified
See 2 more Smart Citations
“…En 2006, los Centros para el Control y la Prevención de Enfermedades de Atlanta, en Estados Unidos (CDC, por sus siglas en inglés) publicaron recomendaciones para mejorar la salud preconcepcional y el cuidado médico 8 . Después, Países Bajos y Canadá han emitido sus propias recomendaciones nacionales para la atención preconcepcional 9 . La OMS, en 2012, presentó el "Plan de acción para acelerar la reducción de la mortalidad materna y mortalidad materna grave", proponiéndose como una medida concreta la organización de los servicios de salud para la atención de la mujer antes del embarazo, continuando con atención del embarazo, parto y puerperio, con el fin de reducir dicha mortalidad 10,11 .…”
Section: Resultsunclassified
“…De acuerdo con la bibliografía revisada [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] , la conceptualización de la atención preconcepcional debe cumplir varias características: darse antes de la concepción con un mínimo de 6 meses, tener seguimiento de acuerdo con la situación de la mujer y la pareja, promocionar la salud antes del embarazo, prevenir riesgos para la madre y el futuro bebé. Lo www.alerta.salud.gob.sv…”
Section: Discussionunclassified
See 1 more Smart Citation
“…The conclusion was obtained from the identification of the health needs of couples in gestational planning in the provinces of Hebei and Jiangsu in China, selected for their marked environmental, geographic and economic differences. 10 In this direction, considering the singularities of each population group, international studies also highlight the needs of specific groups of pregnant women, such as adolescent mothers. A study of their needs, carried out in an educational context in Costa Rica, identified each family as the main source of support for adolescents.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, expansion of the NFPHEP to urbanized China will require significant efforts. Some modifications in the guidelines may also be required depending on local population demographics . Second, this totally free preconception healthcare model is unique in the world, but whether this will be sustainable remains to be seen.…”
Section: Discussionmentioning
confidence: 99%